1993
DOI: 10.1159/000261945
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Language Influence on the Production of Mandarin /f/ and /x/ and Taiwanese /h/ by Native Speakers of Taiwanese Amoy

Abstract: The present study examines the patterns of interference between a first (here, Amoy) and second language (here, Mandarin) by comparing the production of a Mandarin phone [f] (a ‘new’ phone) with another Mandarin phone [x] (which is ‘similar’ to an Amoy phone [h]) by three groups of native Amoy subjects differentiated by proficiency in Mandarin. Their Mandarin production was also compared to that of Mandarin monolinguals. The spectrum of each consonant was analyzed to show the frequency range and energy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
2
9
1
Order By: Relevance
“…There was no effect of L2 Mandarin prosody on the production of L1 Southern Min prosody production in any of the three age groups. This differs from previous findings that, at the segmental level, there are mutual effects of L1 and L2 sound systems in societal bilinguals in vowel (Guion, 2003) and consonant (Peng, 1993) production. The lack of L2-to-L1 impact in the present study is especially notable for the younger speakers, whose Mandarin use was as high as 63% on average (table 1) and who showed clear PFC in their Mandarin.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…There was no effect of L2 Mandarin prosody on the production of L1 Southern Min prosody production in any of the three age groups. This differs from previous findings that, at the segmental level, there are mutual effects of L1 and L2 sound systems in societal bilinguals in vowel (Guion, 2003) and consonant (Peng, 1993) production. The lack of L2-to-L1 impact in the present study is especially notable for the younger speakers, whose Mandarin use was as high as 63% on average (table 1) and who showed clear PFC in their Mandarin.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the factors found to be relevant to immigrant bilinguals have also been confirmed in studies of societal bilinguals, namely those who speak two languages that are both required and used in the community or society (Peng, 1993;Guion et al, 2000a;Guion, 2003). AOL has been found to be one of the most important factors to affect L2 speech production (Piske et al, 2001).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The VOTs of stops were shorter for both languages after several months in Brazil than after several months in the US. Finally, Peng [1993] investigated the production of fricatives by Taiwanese Amoy learners of Mandarin and found that the Amoy [h] of proficient Mandarin speakers showed influence from Mandarin [x].…”
Section: Introductionmentioning
confidence: 99%